2022
DOI: 10.1002/smtd.202101537
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional MXenes for Supercapacitors: A Review

Abstract: However, limited by their high contact resistance, insufficient charge storage, and low electrode density, the activated carbons only show an inadequate capacitance range of 60-200 F cm −3 . [7,8] In comparison, the pseudocapacitive materials, such as conducting polymers and metal oxides, exhibit higher capacitance based on their fast non-diffusion limited surface Faraday redox reactions, [9] whereas poor conductivity and unstable cycle performance restrict their wide-spectrum application. [10,11] Several effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(57 citation statements)
references
References 111 publications
0
57
0
Order By: Relevance
“…It was found that the low Ti 3 C 2 content could improve the specific capacitance of the composites, based on the CV curve integral area data. This might be because the appropriate Ti 3 C 2 content helped to cover the carbon surface evenly, while the excessive Ti 3 C 2 content led to the collapse of the multilayer structure, which is detrimental to ion storage [ 34 ]. Then the gradient sweep velocity of the JSPC&Ti 3 C 2 Tx-1 composite was measured ( Figure 4 b).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the low Ti 3 C 2 content could improve the specific capacitance of the composites, based on the CV curve integral area data. This might be because the appropriate Ti 3 C 2 content helped to cover the carbon surface evenly, while the excessive Ti 3 C 2 content led to the collapse of the multilayer structure, which is detrimental to ion storage [ 34 ]. Then the gradient sweep velocity of the JSPC&Ti 3 C 2 Tx-1 composite was measured ( Figure 4 b).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, developing efficient energy storage systems has become significantly important. Numerous energy storage systems with superior electrochemical performance (long cycle stability and high energy density/power density) have emerged since the first commercialization of rechargeable lithium‐ion batteries in 1990, including sodium‐ion batteries, [ 1–3 ] lithium‐sulfur batteries, [ 4–6 ] aqueous batteries, [ 7,8 ] supercapacitors, [ 9,10 ] and so on. [ 11–16 ] Meanwhile, the batteries often have extremely high energy densities, but they have a short cycle life and safety risks due to severe redox reactions and dendritic complications.…”
Section: Introductionmentioning
confidence: 99%
“…[2] MXenes have a general formula of M n+1 X n T x (n = 1, 2, 3, or 4), where T x represents surface functional groups, such as oxygen ( = O), hydroxyl (-OH) or halogens (-F, -Cl, -Br). [3][4][5][6] To date, various MXenes have been reported in the open literature, such as Ti 3 C 2 , Ti 2 C, Nb 2 C, Nb 4 C 3 , V 2 C, (Ti 0.5 , Nb 0.5 ) 2 C, (V 0.5 , Cr 0.5 ) 3 C 2 , Ti 3 CN, Ta 4 C 3 , and so on. [7] As the parent phase of MXenes, the number of MAX increased from about 50 in 2001 to 155 in 2019.…”
Section: Introductionmentioning
confidence: 99%